Effectiveness of the Demonstration Learning Model In Optimizing Understanding of Islamic Religious Education Materials - Yuyus Susilawati (AIM: Journal of Islamic Education Management, 2025)
Islamic religious education plays a major role in addressing multidimensional crises and character building. Islamic religious education is believed to be able to build positive character and personality. The success of religious education contributes to the preparation of a generation with good ethics, morals, and behavior. However, without a good understanding, it is difficult for students to grow and develop in accordance with the expected values that are the objectives of existing learning. The research method used a qualitative approach with a literature study method. The results of the study show that the demonstration learning model emphasizes the simulation of events, rules, and sequences of activities, either directly or through other relevant media. This is believed to optimize students' understanding of Islamic Religious Education material, so that understanding Islamic values as a strong foundation can shape students' character optimally. The conclusion is that the demonstration learning model can be applied to all subjects, with the aim that students can be more actively involved in understanding and constructing their knowledge, so that understanding Islamic values as a strong foundation can shape the optimal character of students